Development of Web-Based Learning Media Using Google Sites to Improve Learning Outcomes of IPAS - Ulinuha Fatonah; Barokah Isdaryanti (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop a website-based learning media using Google Sites so that it can improve student learning outcomes in science learning grade V elementary school. This development research is carried out according to the ADDIE model. Data collection techniques through interviews, observations, questionnaires, and tests. The data analysis technique uses qualitative and quantitative descriptive and inferential analysis techniques. At the media implementation stage, two trials were carried out, namely a small-scale trial with 5 students and a large-scale trial with 15 students. The result of this research is that the media that has been developed is classified as a very feasible qualification from media experts and material experts. The results of the t-test showed a significant increase in the results of the pre-test and post-test. The results of the N-Gain test showed an increase in the moderate category. Thus, it can be concluded that web-based learning media using Google sites that have been developed can be one of the solutions to improve student learning outcomes